TEST ANXIETY AND ACADEMIC ACHIEVEMENT OF HIGH SCHOOL STUDENTS IN KOKRAJHAR DISTRICT - Roy, Piyali (International Journal of Psychosocial Rehabilitation, 2025)
Test anxiety has become one of the most burning issues of modern school education. Academic Achievement of students is very much depending upon the test anxiety. Present research study was carried out on a sample of 684 high school students. Sample was drawn from different high schools of Kokrajhar District, (Assam)India by employing purposive sampling technique. Analysis was done by calculating simple percentage and Pearson Correlation (r). A wide range of literature review was done before conducting the study. Findings of the study revealed that a significant negative correlation was found between academic achievement and attest anxiety of high school students. Further researches are suggested for more generalised results in relation to other variables like gender, management type of institution, locality, medium of instruction, socio-economic status of the parents etc